The Implementation Challenges Of The Law Concerning Sexual Violence In Indonesia - Rizka Nurliyantika; Aisyah Wardatul Jannah (Simbur Cahaya, 2023)
The law concerning the crime of sexual violence came into force on 22 April 2022 as law number 12, the year of 2022 has been waiting by most of the society in Indonesia with the hope that this regulation may reduce or even dispel the crime of sexual violence, which increased currently. However, some argue that some articles in the act contain a provision that contradicted religious norms and social morals even though some consider this act as a form of pure liberalization in Indonesia. The method of this research uses a normative juridical method and is supported by conceptual by analysing the view or concept of the jurist on and statute approach to defending the argumentation on the legal and data materials. The result shows that the act (UU TPKS) has a role as supplementary rules under Indonesian criminal code to settle the cases of sexual violence in Indonesia, and as legal protection to the victim of sexual violence. On the contrary, several challenge might occur in the implementation, such as internal problems from the legal enforcement itself, lack of implementing regulations and arises of the conservatism society which, holds a patriarchal understanding of how the populace considers sexual violence.